Early Blood Biomarkers to Improve Sepsis/Bacteremia Diagnostics in Pediatric Emergency Settings - Emilija Tamelytė; Gineta Vaičekauskienė; Algirdas Dagys; Tomas Lapinskas; Lina Jankauskaitė (Medicina, 2019)
Background: Sepsis is the leading cause of death in children worldwide. Early recognition and treatment are essential for preventing progression to lethal outcomes. CRP and Complete Blood Count (CBC) are the initial preferred tests to distinguish between bacterial and viral infections. Specific early diagnostic markers are still missing. Aim: To investigate diagnostic value of Neutrophil–Lymphocyte Ratio (NLR), Mean Platelet Volume (MPV) and Platelet–MPV ratio (PLT/MPV) to distinguish sepsis/bacteremia and viral infection. Methods: We conducted a retrospective data analysis of case records of 115 children from 1 month to 5 years of age. All cases were divided into two groups—sepsis/bacteremia (n = 68) and viral (n = 47) patients, and further subdivided according to the time of arrival into early or late (≤12 or 12–48 h post the onset of fever, respectively). Analysis of CBC and CRP results was performed. NLR and PLT/MPV were calculated. Results: Sepsis/bacteremia group demonstrated higher absolute platelets count (370.15 ± 134.65 × 109/L versus 288.91 ± 107.14 × 109/L; p = 0.001), NLR (2.69 ± 2.03 versus 1.83 ± 1.70; p = 0.006), and PLT/MPV (41.42 ± 15.86 versus 33.45 ± 17.97; p = 0.001). PLT/MPV was increased in early arrival sepsis/bacteremia infants (42.70 ± 8.57 versus 31.01 ± 8.21; p = 0.008). NLR and MPV were significantly lower in infants (≤12 months) with viral infection on late arrival (1.16 ± 1.06 versus 1.90 ± 1.25, p = 0.025 for NLR and 8.94 ± 0.95fl versus 9.44 ± 0.85fl, p = 0.046 for MPV). Conclusion: Together with standard blood biomarkers, such as CRP, neutrophils, or platelets count, PLT/MPV is a promising biomarker for clinical practice to help discriminate between viral disease or sepsis/bacteremia in all children, especially in early onset of symptoms. NLR and MPV could support exclusion of sepsis/bacteremia in late arrival cases.